Double-Balloon Remodeling of Wide-Necked Aneurysms Distal to the Circle of Willis - Arat, Anil; Cil, Barbaros (American Journal of Neuroradiology, 2005)
Summary: We describe a remodeling technique in which two compliant balloon catheters were used to treat large, wide-necked bifurcation aneurysms distal to the circle of Willis in two patients with subarachnoid hemorrhage. Although vasospasm and interaction between the constrained catheters in the small distal arteries added to the complexity of the procedure, placement of a balloon catheter in each side branch prevented coil encroachment and enabled embolization of these aneurysms.